Alive Borned Parapagus Dicephalus Conjoined Twins at Term: A Case Report - Ilhan, Tolgay Tuyan; Ilhan, Turkan (Fırat University, 2013)
Parapagus dicephalus conjoined twins are rare but severe complication of multigestational pregnancies. Many conjoined twin pregnancies are diagnosed before reaching viability. We present a case report of conjoined twins reached term. A 35-year-old pregnant woman, who had no prenatal follow up, delivered conjoined twins at Van Maternity Hospital. The total weight of the fetuses was 4750 g. and they could be alive without advance support. Conjoined fetuses can be detected on prenatal screening and ultrasound. This case reinforces the importance of prenatal follow up.

Parapagus dicephalus yapışık ikizler çoğul gebeliklerin nadir fakat ciddi komplikasyonlarıdır. Yapışık ikizlerin birçoğuna yaşayabilir büyüklüğe erişmeden tanı konulmaktadır. Biz miadına kadar erişmiş bir vakayı sunmak istiyoruz. Otuzbeş yaşında prenatal takibi olmayan gebe Van Doğumevi' nde yapışık ikiz doğurmuştur. Fetusların toplam ağırlığı 4750 gramdır ve ciddi bir yaşam desteği sağlanmadan hayatta kalmışlardır. Yapışık ikizler prenatal tarama ve ultrasonla tespit edilebilmektedir. Bu olgu prenatal değerlendirmenin önemini desteklemektedir.
Miadında Canlı Doğan Parapagus Dicephalus Yapışık İkiz: Olgu Sunumu